Assessing the acceptability of an adapted preschool obesity prevention programme: ToyBox‐Scotland. (15th January 2020) - Malden, Stephen; Reilly, John J.; Hughes, Adrienne; Bardid, Farid; Summerbell, Carolyn; De Craemer, Marieke; Cardon, Greet; Androutsos, Odysseas; Manios, Yannis; Gibson, Ann‐Marie
Abstract: Background: Childhood obesity is a global public health issue. Interventions to prevent the onset of obesity in the early years are often implemented in preschool settings. The ToyBox intervention was delivered across Europe and targeted energy balance‐related behaviours in preschools and children's homes through teacher‐led activities and parental education materials and was adapted for use in Scotland. This study assessed the acceptability of the 18‐week adapted intervention to both parents and teachers. Methods: Mixed methods were employed to collect both qualitative and quantitative data. Preschool staff and children's parents/caregivers completed post‐intervention feedback surveys, from which acceptability scores were calculated and presented as proportions. Focus groups were conducted with preschool staff, whereas parents/caregivers participated in semi‐structured interviews. A thematic analysis was applied to qualitative data following the development of a coding framework. Quantitative and qualitative data were analysed using SPSS and NVivo 10, respectively. Results: Preschool staff rated the intervention as highly acceptable based on post‐intervention feedback surveys (80%; mean score 8.8/11). Lower acceptability scores were observed for parents/caregivers (49%; 3.9/8). Nine preschool practitioners participated in focus groups ( n = 3). User‐friendliness of the intervention materials, integration of the intervention with the curriculum, and flexibility of the intervention were identified as facilitators to delivery. Barriers to delivery were time, insufficient space, and conflicting policies within preschools with regard to changing classroom layouts. Parental interviews ( n = 4) revealed a lack of time to be a major barrier, which prevented parents from participating in home‐based activities. Parents perceived the materials to be simple to understand and visually appealing. Conclusions: This study identified a number of barriers and facilitators to the delivery and evaluation of the ToyBox Scotland preschool obesity prevention programme, which should be considered before any further scale‐up of the intervention.